2017
DOI: 10.20307/nps.2017.23.4.247
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Methylglyoxal Trapping Constituents from Onion Peels by Pre-column Incubation Method

Abstract: − The methylglyoxal (MGO) trapping constituents from onion (Allium cepa L.) peels were investigated using pre-column incubation of MGO and crude extract followed by HPLC analysis. The peak areas of MGO trapping compounds decreased, and their chemical structures were identified by HPLC-ESI/MS. Among major constituents in outer scale of onion, 2-(3,4-dihydroxybenzoyl)-2,4,6-trihydroxy-3(2H)-benzofuranone (2) was more effective MGO scavenger than quercetin (6) and its 4'-glucoside, spiraeoside (3). After 1 h incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Zhang, Wang, and Liu [31] observed that after reaction with MGO (5 mM), robinin, procyanidins, luteolin, quercetin, chrysoeriol, kaempferol, genistein, apigenin, and rutin at 5 mM showed capture percentage values of 54.4%, 46.3%, 40.7%, 21.4%, 41.8%, 58.9%, 43.4%, 36.5%, and 49.3%, respectively, values lower than those found in this work for PIC (65.1%, 2 mM). In another study, with ethanolic extract of onion peel (0.5 mg/mL), it was observed elimination of approximately 70% of MGO (0.33 mM) after 1 h of reaction, an excellent capture potential [32], while the methanolic extracts of berries and grapes, using a similar method, showed from 20% to 50% of MGO (10 mM) capture potential. Raspberry, strawberry, blackberry, cranberry, blueberry, and noble grape at a concentration of 2.5 mg/mL showed capture potential of 20%, 30%, 45%, 50%, and 50%, respectively, after 1 h of reaction with MGO [33].…”
Section: Inhibition Of Age In the Initial And Intermediate States Of ...mentioning
confidence: 91%
“…Zhang, Wang, and Liu [31] observed that after reaction with MGO (5 mM), robinin, procyanidins, luteolin, quercetin, chrysoeriol, kaempferol, genistein, apigenin, and rutin at 5 mM showed capture percentage values of 54.4%, 46.3%, 40.7%, 21.4%, 41.8%, 58.9%, 43.4%, 36.5%, and 49.3%, respectively, values lower than those found in this work for PIC (65.1%, 2 mM). In another study, with ethanolic extract of onion peel (0.5 mg/mL), it was observed elimination of approximately 70% of MGO (0.33 mM) after 1 h of reaction, an excellent capture potential [32], while the methanolic extracts of berries and grapes, using a similar method, showed from 20% to 50% of MGO (10 mM) capture potential. Raspberry, strawberry, blackberry, cranberry, blueberry, and noble grape at a concentration of 2.5 mg/mL showed capture potential of 20%, 30%, 45%, 50%, and 50%, respectively, after 1 h of reaction with MGO [33].…”
Section: Inhibition Of Age In the Initial And Intermediate States Of ...mentioning
confidence: 91%
“…After incubation, o-phenylene diamine (derivatization agent, 10 mmol/L) was added to each sample, and the mixtures were kept at room temperature for 30 min for derivatization of the remaining MGO. Levels of remaining MGO were then measured as previously described [43].…”
Section: Methodsmentioning
confidence: 99%
“…Due to the structural similarity to metformin, the galegine present in G. officinalis may demonstrate analogy RCS trapping activity. Moreover, many recent studies have reported that other groups of phytochemicals commonly occurring in plants-e.g., flavonoids and phenolic acids-also scavenge RCS and free radicals such as reactive oxygen species (ROS), which both demonstrate a prominent role in the pathogenesis of endothelial dysfunction related to diabetes mellitus [22,23] However, although the therapeutic properties of goat's rue have long been recognized and appreciated in traditional medicine, the study of the phytochemical profile of the G. officinalis herb has been barely addressed. Previous studies on the composition of this species were focused on seed phytochemistry, mainly concerning amino compounds [24].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the structural similarity to metformin, the galegine present in G. officinalis may demonstrate analogy RCS trapping activity. Moreover, many recent studies have reported that other groups of phytochemicals commonly occurring in plants—e.g., flavonoids and phenolic acids—also scavenge RCS and free radicals such as reactive oxygen species (ROS), which both demonstrate a prominent role in the pathogenesis of endothelial dysfunction related to diabetes mellitus [ 22 , 23 ]…”
Section: Introductionmentioning
confidence: 99%